2002
DOI: 10.1021/bi012179b
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Requirements for Structure and Catalysis of an RNA Ligase Ribozyme

Abstract: The class I ligase, a ribozyme previously isolated from random sequence, catalyzes a reaction similar to RNA polymerization, positioning its 5′-nucleotide via a Watson-Crick base pair, forming a 3′,5′-phosphodiester bond between its 5′-nucleotide and the substrate, and releasing pyrophosphate. Like most ribozymes, it requires metal ions for structure and catalysis. Here, we report the ionic requirements of this self-ligating ribozyme. 2+ and Co(NH 3 ) 6 3+ inhibit by binding at least two sites, but they appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 69 publications
(128 reference statements)
3
47
0
Order By: Relevance
“…In principle, a metal rescue experiment could lend support to the role of some of these oxygens as inner-sphere ligands (Piccirilli et al 1993). However, the ligase is strongly inhibited by the transition metals that are the best candidates for metal rescue (Glasner et al 2002); pilot experiments confirmed that this line of inquiry was unlikely to be productive (data not shown). Instead, the improved ligase crystal structure (Shechner et al 2009) provided a framework for interpreting the interference maps.…”
Section: Interference Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…In principle, a metal rescue experiment could lend support to the role of some of these oxygens as inner-sphere ligands (Piccirilli et al 1993). However, the ligase is strongly inhibited by the transition metals that are the best candidates for metal rescue (Glasner et al 2002); pilot experiments confirmed that this line of inquiry was unlikely to be productive (data not shown). Instead, the improved ligase crystal structure (Shechner et al 2009) provided a framework for interpreting the interference maps.…”
Section: Interference Mappingmentioning
confidence: 99%
“…Buffers were the same as described for selection. KCl (200 mM) was included in initial experiments, but omitted in experiments measuring the Mg 2+ -dependence of ligation, and in all reactions in which the concentration of Mg 2+ was <10 mM, because at low Mg 2+ concentration it inhibits the parent ligase (Glasner et al 2002). Omitting KCl did not affect rates of either parent or clones at $10 mM Mg 2+ .…”
Section: Kinetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in principle this approach is general to large ribozymes that use extensive Watson-Crick base pairs, we developed it using the extensively characterized Class I ligase motif of Bartel and colleagues Bergman et al 2000;Glasner et al 2000Glasner et al , 2002.…”
Section: Half-ribozymesmentioning
confidence: 99%